A common transcriptional mechanism involving R-loop and RNA abasic site regulates an enhancer RNA of APOE. Issue 21 (1st December 2022) - Watts, Jason A; Grunseich, Christopher; Rodriguez, Yesenia; Liu, Yaojuan; Li, Dongjun; Burdick, Joshua T; Bruzel, Alan; Crouch, Robert J; Mahley, Robert W; Wilson, Samuel H; Cheung, Vivian G
Abstract: RNA is modified by hundreds of chemical reactions and folds into innumerable shapes. However, the regulatory role of RNA sequence and structure and how dysregulation leads to diseases remain largely unknown. Here, we uncovered a mechanism where RNA abasic sites in R-loops regulate transcription by pausing RNA polymerase II. We found an enhancer RNA, AANCR, that regulates the transcription and expression of apolipoprotein E ( APOE ). In some human cells such as fibroblasts, AANCR is folded into an R-loop and modified by N-glycosidic cleavage; in this form, AANCR is a partially transcribed nonfunctional enhancer and APOE is not expressed. In contrast, in other cell types including hepatocytes and under stress, AANCR does not form a stable R-loop as its sequence is not modified, so it is transcribed into a full-length enhancer that promotes APOE expression. DNA sequence variants in AANCR are associated significantly with APOE expression and Alzheimer's Disease, thus AANCR is a modifier of Alzheimer's Disease. Besides AANCR, thousands of noncoding RNAs are regulated by abasic sites in R-loops. Together our data reveal the essentiality of the folding and modification of RNA in cellular regulation and demonstrate that dysregulation underlies common complex diseases such as Alzheimer's disease.